IMPLEMENTASI PENILAIAN AUTENTIK BERBASIS KURIKULUM 2013 DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN - Febrian Alwan Bahrudin; Stevany Afrizal (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This research examines Authentic Assessment Based on Curriculum 2013 in Pancasila and Citizenship Education Subject where is located at Senior High School (SMA) Negeri 15 Pandeglang Banten. The objective of this research is to determine the implementation of authentic assessment based on curriculum 2013 in Pancasila and Citizenship Education subject which consist of cognitive, affective, and psychomotor assessments. In this research, the writer uses qualitative approach and descriptive method. The results indicate that authentic assessment in the Cognitive Aspect can be done by several types of tests: written tests, oral tests, and assignments. In the written test, there are Daily Assessment (PH), Mid-Semester Assessment (PTS), Final Semester Assessment (PAS), and also End-of-Year Assessment (PAT). Moreover, psychomotor assessments consist of performance appraisal, project appraisal, and also portofolio assessment. The Final authentic assessment based on curriculum 2013 in Pancasila and Citizenship Education Subjects is Affective assessment: observation, self-assessment, peer-to-peer assessment, and also journals. In this aspect, students are hoped to be able to implement a good personality following the values of Pancasila and the 1945 Constitution as a form of reflection of good citizen in Indonesia. Keywords: Pancasila and Citizenship Education. Authentic Assessment, Curriculum 2013